The Biological Camera from Kidney of Human Beings - Sunte, Jitendra (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
This paper deals with the subject principle of cameras as biological cameras and physical cameras, which may present many materials for assembly. Here, the human body’s kidney is taken as a major component, and the iris is placed on one of the surfaces of the kidney, and it works the same as the human eye, which is one of the biological cameras. This is how the procedure is carried out to construct the camera. As you need so many materials to exhibit the camera, whether they are physics materials or biological materials in general, all materials exhibit the camera.